Young children's story schema and their receptive, expressive and performative engagement toward storybook read alouds - Africa, Cherry Pua- (2005)
This qualitative study analyzed the patterns and polarities of young children's receptive, expressive and performative responses and explored their prior knowledge and how well they use stories as a strategic way of assimilating and accommodating concepts to provide a bigger scope by which they can view the world around them. Results identified the following factors as influencing a child's schema: their own experiences; their accumulated readings of text; technology and through pictures and texts found in stories. Narratives helped expand the schema of young children. The study helped identify the various responses of young children toward read alouds. It also demonstrated how young children engage in various level of text-related thinking such as identifying or inferring causality, motive, character thoughts and feelings, comparison/contrast, and inferring events and actions not specifically described in the text.